2011
DOI: 10.1111/j.1708-8208.2009.00189.x
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional Tolerances and Assembly Accuracy of Dental Implants and Machined Versus Cast‐On Abutments

Abstract: An original measuring protocol was developed, independent of parts assembly and based on ITs. An objective dimensional characterization of prosthetic components and assemblies has been achieved, which is the basis for their reliability in clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 8 publications
5
17
0
Order By: Relevance
“…The applied torque and the masticatory load could generate micromovements, deforming the implant hexagon. Studies have indicated a direct correlation between implant-abutment rotational misfit and screw loosening [9][10][11][12] . Preload is the tension on a screw generated when a torqueing force is applied to the screw head.…”
Section: Introductionmentioning
confidence: 99%
“…The applied torque and the masticatory load could generate micromovements, deforming the implant hexagon. Studies have indicated a direct correlation between implant-abutment rotational misfit and screw loosening [9][10][11][12] . Preload is the tension on a screw generated when a torqueing force is applied to the screw head.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the implants were inserted in self-curing acrylic resin rigid plates in pattern way using liners. It enables a specimen evaluation with appropriately fixed on the acrylic in order to decease external variables that could interfere on the results, as bone type and quality, implant thread macro and micro geometry and eve implant surface treatment [25][26][27][28][29][30] . .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, despite the torque application have caused dimensional changes on the hexagon surface, most of torques applied did not showed significant change. However, it is known that when there is significant change, pillar implant adaptation can be directly affected and some studies have showed a close relation between p r o s t h e s i s m i s m a t c h a n d b o l t s loosening [25][26][27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…There are very few papers exploring thread milling forces on titanium alloys although it is been widely used for medical and dental implants [Malaguti et al, 2011], [Lopez-Heredia et al, 2008] e [Yamazoe, 2010].…”
Section: Introductionmentioning
confidence: 99%